The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/healthcare8030329
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Healthcare Use and Costs—A Systematic Review

Abstract: Background: Thus far, there is a lack of a systematic review synthesizing empirical studies that analyze the link between personality factors and healthcare use (HCU) or costs. Consequently, the purpose of our systematic review is to give an overview of empirical findings from observational studies examining the association between personality factors and HCU or costs. Methods: PubMed, PsycINFO, and NHS EED (NHS Economic Evaluation Database) were searched. Observational studies examining the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…There is also evidence that higher neuroticism increases rates of forgone healthcare. This finding concords with research suggesting that individuals higher in neuroticism tend to seek out more medical appointments and visits (Hajek et al, 2017(Hajek et al, , 2020, raising the amounts of potential medical services that might be forgone. Furthermore, higher neuroticism might accentuate feelings of risk regarding potential COVID-19 infection, raising the probability that a medical service is forgone to avoid possible infection.…”
Section: Individual-level Predictorscontrasting
confidence: 55%
See 1 more Smart Citation
“…There is also evidence that higher neuroticism increases rates of forgone healthcare. This finding concords with research suggesting that individuals higher in neuroticism tend to seek out more medical appointments and visits (Hajek et al, 2017(Hajek et al, , 2020, raising the amounts of potential medical services that might be forgone. Furthermore, higher neuroticism might accentuate feelings of risk regarding potential COVID-19 infection, raising the probability that a medical service is forgone to avoid possible infection.…”
Section: Individual-level Predictorscontrasting
confidence: 55%
“…Self-perceived health relates closely to morbidity and indicates need for regular medical care. Neuroticism has been associated with increased medical appointments and visits (Hajek et al, 2017(Hajek et al, , 2020. Beyond perceived need for medical care, neuroticism might affect sentiments of risk of COVID-19 infection during medical appointments and treatments.…”
Section: Control Variablesmentioning
confidence: 99%
“…Similarly, we cannot generalize our results to older individuals living in rural settings. Lastly, the possibility cannot be dismissed that other factors may exist that contribute to persistent frequent attendance among the oldest old [e.g., neuroticism ( 46 )].…”
Section: Discussionmentioning
confidence: 99%
“…Even after adjusting for the factors included in the Andersen model, previous studies have demonstrated that psychosocial factors or personality-related factors are important for HCU 3–6. Nevertheless, the association between purpose in life and HCU remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%